Трипільська культура — 110 років досліджень - Бурдо, Н.Б. (Археологія, 2005)
Статтю присвячено огляду головних досягнень у дослідженні трипільської культури за 110 років з часу її відкриття В.В. Хвойкою. Годом открытия трипольской культуры является условная дата — 1893 год. Именно тогда В.В. Хвойка открыл в Киеве неолитическое поселение на Кирилловской улице. В дальнейшем раскопки аналогичных памятников исследователь провел вокруг местечка Триполье, которое и дало название археологической культуре, оставленной древнейшим земледельческим населением Восточной Европы.
В первые десятилетия изучения выяснилось, что памятники, аналогичные открытым В.В. Хвойкой возле Триполья, известны в лесостепной полосе от Бессарабии до Поднепровья. В начале ХХ в. трипольские поселения исследовались на территории двух империй — Российской и Австро-Венгерской. В Советском Союзе памятники трипольской культуры изучали археологи Киева, Москвы, Ленинграда, Одессы, Кишинева. Продолжаются исследования трипольской культуры и в независимой Украине. Спустя сто лет не только неизмеримо выросла источниковедческая база трипольеведения, но и коренным образом изменились представления об этой культуре, которая имеет большое значение для древней истории Юго-Восточной Европы. The year of discovery of the Trypillia culture — 1893 — is conventional. That’s when VV Hvoika explored a Neolithic settlement on the Kyryllivska Str. in Kyiv. Later on the researcher excavated analogous monuments around a small town of Trypillia after which the archaeological culture of the earliest agricultural population of the Eastern Europe was called.
During the first decades of research it was revealed that the monuments analogous to those discovered by V.V. Hvoika near Trypillia are known in the forest-steppe zone from Bessarabia to the Dnipro River region. In the early 20th century the Trypillia settlements were surveyed on the territory of two Empires — Russian and Austro-Hungarian. In the Soviet time the Trypillya culture monuments were studied by the archaeologists from Kyiv, Moscow, Leningrad, Odessa, Kishiniv. Independent Ukraine also continues the study of the Trypillia culture. During this century not only the Trypillia culture source study base has increased immeasurably, but also the views upon this culture, which is of great importance for the ancient history of the Southeastern Europe, have changed fundamentally.